(untitled) (Agro-Science Letters, 2026)
Agricultural Extension (AE) serves as a cornerstone of contemporary farming by bridging the gap between scientific knowledge generated at research institutions and the practical needs of farmers, ultimately driving improvements in agricultural productivity and long-term sustainability. Its significance is amplified in the current era, where the compounding pressures of climate variability and volatile market conditions require farmers to be adaptive and responsive. AE functions as a conduit through which advances in crop management, farming technologies, and scientific innovations are made accessible to farming communities, including those in geographically isolated and resource-limited areas. This review explores the multifaceted contributions of AE to Indian agriculture, with particular attention to its roles in translating research outputs for farmers, building technical capacities, guiding efficient production strategies, and strengthening resilience against environmental and economic risks. As India confronts growing threats from climate change alongside persistent food security concerns, AE assumes an even more critical function. Emerging digital tools such as artificial intelligence platforms and immersive virtual technologies offer transformative possibilities for delivering extension services; however, their adoption must be guided by principles of inclusivity, particularly in addressing unequal access to digital infrastructure and varying levels of digital competency among farming populations. Structural barriers including insufficient funding, socio-cultural constraints, and fragmented policy frameworks continue to challenge the effectiveness of extension systems. Addressing these requires sustained innovation and systemic reforms. Going forward, AE will remain indispensable in navigating the evolving agricultural landscape of India, with continued investment needed to enhance its reach and responsiveness.